THE CELLULAR ANTIGENS OF GROUP A STREPTOCOCCI : IMMUNOELECTROPHORETIC STUDIES OF THE C, M, T, PGP, E(4), F, AND E ANTIGENS OF SEROTYPE 17 STREPTOCOCCI - Wilson, Armine T. (The Rockefeller University Press, 1963)
The immunoelectrophoretic characteristics of the known cellular antigens of serotype 17, Group A streptococci have been presented. These include C, M, T, and polyglycerophosphate. In addition, three hitherto undescribed antigens of serotype 17 have been encountered. The F antigen occurs in most serotype 17 strains, has a faster electrophoretic mobility than M, appears in acid, distilled water, and other extracts of harvested cells, is released from the cells in large quantity into the culture medium during growth when the pH is maintained at 7.3 or over, is probably protein in nature, and may play a minor role in mouse virulence of serotype 17 strains. Its antibodies do not confer bactericidal power on human blood. The E antigen is serotype-specific and is closely associated with the M antigen. The suggestion is made here that E is a part of the M molecule, acquiring independent electrophoretic mobility when separated from the rest of the M molecule by acid hydrolysis and carrying an antigenic determinant serologically distinct from the determinant on the rest of the M molecule. E can be recognized only by immunoelectrophoresis. Its role, if any, in virulence has not been established. The third antigen, E(4), is a non-serotype-specific antigen found in most serological groups and types of hemolytic streptococci. It is serologically related to polyglycerophosphate, but its chemical nature has not been determined. It appears to be unrelated to virulence.